Sosialisasi Pemanfaatan Bahan Ajar Berbasis Multimedia - Bagus Priambodo; Nur Ani; Sarwati Rahayu; Rinto Priambodo; Inge Handriani; Anita Ratnasari; Yuwan Jumaryadi; Nia Rahma Kurnianda (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Today's rapidly developing technology makes it easier for humans to do their work. Education is the main thing in educating children in a country so that they can perform well and in accordance with normative values. In the world of education we can do many things as a source of learning not only books, but also by utilizing the environment around us. Apart from the environment, we can also use digital media as a source of learning to make it easier. The development of a curriculum has always been the main focus and continues to be carried out to improve and respond to community needs so that the socialization of the use of multimedia applications is felt to be very useful for improving the quality of learning media. In this community service activity, we conducted socialization regarding the use of several multimedia applications at the Early Childhood Education Cluster Activity Center (PKG) in Sukaraja District. Based on the results of the questionnaire given after the activity, the activities carried out were very useful to support the teaching activities carried out.